Mobile learning development for supporting computer programming skills - Krittawaya Thongkoo (2018)
© Springer Science+Business Media Singapore 2016. This is so difficult for the first year students to start to write computer program in the subject of writing basic computer program due to most of students don’t have a good basic of sciences and mathematics including lack of interesting in the subject processes related to writing Programming Assistance Instrument, which is web application that can help to motivate students to learn about writing fundamental program efficiency. This will help to increase learning skills and related to idea for students to write computer program very well. This research has proposed that the first year students, which are learning in Modern Management and Information Technology (MMIT) Course of College of Arts, Media and Technology should receive the contribution in writing computer program with this Programming Assistance Instrument that the main objective of this research is the contribution of knowledge include helping MMIT students to understand the idea of writing basic computer program in order to have motivation to learn and write further other computer programs. The expected result that should be received is the students who have use Programming Assistance Instrument will get knowledge, understanding and motivation in writing computer program better than students who studied with the old method.